Penerapan Model Realistic Mathematics Education (RME) Untuk Meningkatkan Kemampuan Pemahaman Konsep Siswa Kelas IV Sekolah Dasar Mata Pelajaran Matematika - Shelvi Assholelehah, Aprillia; Dwi Pratama, Yoga (Science and Education Journal (SICEDU), 2025)
The background of this research is the low ability of students to understand mathematical concepts in grade 4. This research aims to improve the ability to understand the concept of grade 4 students of UPT SDN 005 Langgini. This research is a classroom action research (PTK), which is carried out in two cycles and each cycle consists of two meetings. The subjects in this study are all 4th grade students totaling 18 students. Data collection techniques are in the form of interviews, observations, documentation and tests. Meanwhile, the data analysis technique used is a combination of qualitative data and quantitative data. Based on the results of the research that has been carried out through 2 cycles, in the 1st meeting of the first cycle of students who completed there were 8 students with a percentage of 44.44% with an overall average of 65.83 and in meeting 2 it increased to 10 students with a percentage of 55.55% with an overall average of 71.38%. Meanwhile, in the second cycle of the 1st student meeting, there were 13 students with a percentage of 72.22% with an overall average of 82.5% and there was an increase in meeting 2 to 16 students with a percentage of 88.88% with an overall average of 85.22. Based on the results of this study, it shows that by implementing Think Pair Share learning, it can improve the ability to understand mathematical concepts of 4th grade students of UPT SDN 005 Langgini.